A Novel Approach to Improve GNSS Precise Point Positioning during Strong Ionospheric Scintillation: Theory and Demonstration - Vani, Bruno Cesar; Forte, Biagio; Monico, Joao Francisco Galera [UNESP]; Skone, Susan; Shimabukuro, Milton Hirokazu [UNESP]; Moraes, Alison De Oliveira; Portella, Igor Ponte; Marques, Haroldo Antonio (My University, 2019)
At equatorial latitudes, ionospheric scintillation is the major limitation in achieving high-accuracy GNSS positioning. This is because scintillation affects the tracking ability of GNSS receivers causing losses of lock and degradation on code pseudorange and carrier phase measurements, thus degrading accuracy. During strong ionospheric scintillation, such effects are more severe and GNSS users cannot rely on the integrity, reliability, and availability required for safety-critical applications. In this paper, we propose a novel approach able to greatly reduce these effects of scintillation on precise point positioning (PPP). Our new approach consists of three steps: 1) a new functional model that corrects the effects of range errors in the observables; 2) a new stochastic model that uses these corrections to generate more accurate positioning; and 3) a new strategy to attenuate the effects of losses of lock and consequent ambiguities re-initializations that are caused by the need to re-initialize the tracking. We demonstrate the effectiveness of our method in an experiment using a 30-day static dataset affected by different levels of scintillation in the Brazilian southeastern region. Even with limitations imposed by data gaps, our results demonstrate improvements of up to 80% in the positioning accuracy. We show that, in the best cases, our method can completely negate the effects of ionospheric scintillation and can recover the original PPP accuracy that would have existed without any scintillation. The significance of this paper lies in the improvement it offers in the integrity, reliability, and availability of GNSS services and applications.
Keywords: Ionospheric scintillation; mitigation; precise point positioning (PPP); scintillation-induced error